Harnessing climate informed digital crop intelligence technologies is key to building the resilience of food systems against climate change in the SADC region - Amha, Yosef; Afiesimama, Ernest; Murombedzi, James; Garanganga, Bradwell; Demissie, Teferi Dejene; Magagula, Futhi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Climate-informed crop intelligence technologies are vital for building the resilience of food systems against the impacts of extremes in climate variation and climate change. As a result, agricultural policymakers, practitioners, and planners have used them to make tactical and strategic decisions, including estimating agricultural inputs needed months before the crop-growing season, selecting potential management practices, estimating crop performance and yields under various seasonal climate forecast scenarios, and providing anticipatory options against climate change. They may also be used in crop insurance evaluation schemes since they track real-time crop growth and estimate yield loss. Such tools are especially important in the SADC region, where severe weather and climate shocks have become more frequent and stronger in recent years, with catastrophic effects on livelihoods, food security, agriculture, human habitations, and ecosystems. As a result, the regional partners developed a user-friendly crop capability prediction tool and then conducted a series of capacity-building training in the SADC region. This capacity-building activity, however, requires the full cooperation of relevant national and regional organizations, initiatives, and governments in the region to be sustainable and have a long-term impact.